Analisis Hubungan Kausalitas Antara Tingkat Pendidikan, Tingkat Pengangguran Terbuka, Pdrb Per Kapita, Dan Persentase Penduduk Miskin Di Provinsi Papua - Rahayu, Sekar Eka; Samsuddin, M. Afdal (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the causality relationship between the level of education (measured through Average Years of Schooling), Open Unemployment Rate (TPT), Gross Regional Domestic Product (GRDP) per capita, and the percentage of poor people in Papua Province. The data used is secondary quarterly time series data for the period 2015-2023 using the Vector Error Correction Model (VECM) methods. The stationarity test results show that all variables are stationary at the 2nd difference level, while the optimal lag test selects lag 4 as the best lag. The stability test proves that the model used is stable and valid. The Granger Causality test shows no significant short-term causality between variables, but the Johansen cointegration test proves a significant long-term relationship. The VECM estimation shows significant error correction term coefficients on some of the main variables, indicating the existence of an adjustment mechanism towards long-term equilibrium. IRF and Variance Decomposition (VD) results show each variable is most responsive to shocks from itself, but there are also inter-variable influences in the long run. These findings emphasize the importance of integrated development policies to reduce poverty in Papua in a sustainable manner.